Compression socks and the effects on coagulation and fibrinolytic activation during marathon running - Zadow, E. K.; Adams, M. J.; Wu, S. S. X.; Kitic, C. M.; Singh, I.; Kundur, A.; Bost, N.; Johnston, A. N. B.; Crilly, J.; Bulmer, A. C.; Halson, S. L.; Fell, J. W. (European Journal of Applied Physiology, 2018)
Purpose: Compression socks are frequently used in the treatment and prevention of lower-limb pathologies; however, when combined with endurance-based exercise, the impact of compression socks on haemostatic activation remains unclear. Objectives: To investigate the effect of wearing compression socks on coagulation and fibrinolysis following a marathon. Methods: Sixty-seven participants [43 males (mean ± SD: age: 46.7 ± 10.3 year) and 24 females (age: 40.0 ± 11.0 year)] were allocated into a compression (SOCK, n = 34) or control (CONTROL, n = 33) group. Venous blood samples were obtained 24 h prior to and immediately POST-marathon, and were analyzed for thrombin-anti-thrombin complex (TAT), tissue factor (TF), tissue factor pathway inhibitor (TFPI), and D-Dimer. Results: Compression significantly attenuated the post-exercise increase in D-Dimer compared to the control group [median (range) SOCK: + 9.02 (- 0.34 to 60.7) ng/mL, CONTROL: + 25.48 (0.95-73.24) ng/mL]. TF increased following the marathon run [median (range), SOCK: + 1.19 (- 7.47 to 9.11) pg/mL, CONTROL: + 3.47 (- 5.01 to 38.56) pg/mL] in all runners. No significant post-exercise changes were observed for TAT and TFPI. Conclusions: While activation of coagulation and fibrinolysis was apparent in all runners POST-marathon, wearing compression socks was shown to reduce fibrinolytic activity, as demonstrated by lower D-Dimer concentrations. Compression may reduce exercise-associated haemostatic activation when completing prolonged exercise.